Discovery of a reversible redox-induced order-disorder transition in a 10-component compositionally complex ceramic. (1st July 2022) - Zhang, Dawei; Chen, Yan; Feng, Tianshi; Yu, Dunji; An, Ke; Chen, Renkun; Luo, Jian
Highlights: A reversible redox-induced order-disorder transition (ODT) is discovered. A 10-component single-phase ordered pyrochlore oxide is stable at 1600 °C in air. Reduction at 1600 °C induces an ODT to form single-phase disordered fluorite oxide. Re -oxidation at 1600 °C reverses the ODT to form single-phase ordered pyrochlore. In-situ neutron diffraction reveals the mechanism of oxygen vacancy induced ODT. Abstract: This study discovers a reversible order-disorder transition (ODT) in a 10-component compositionally complex ceramic, (Nd0.15 Pr0.15 Dy0.8 Ho0.8 Er0.8 Ti0.2 Yb0.1 Hf0.1 Zr0.1 Nb0.8 )O7-δ, induced via annealing in oxidized vs. reduced environments at 1600 °C. Notably, the 10-cation oxide remains a homogenous single-phase high-entropy solid solution before and after the ODT in the pyrochlore vs. fluorite structure that can be quenched. In-situ neutron diffraction reveals the oxygen vacancy formation and atomic displacement during this ODT. This study reveals a new pathway to induce ODT via a redox transition to tailor the properties of compositionally complex fluorite-based oxides. Graphical abstract: Image, graphical abstract